2016
DOI: 10.1007/s12035-016-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms

Abstract: Stress experience modulates behavior, metabolism, and energy expenditure of organisms. One molecular hallmark of an acute stress response is a rapid induction of immediate early genes (IEGs) such as c-Fos and Egr family members. IEG transcription in neurons is mediated by the neuronal activity-driven gene regulator serum response factor (SRF). We show a first role of SRF in immediate and long-lasting acute restraint stress (AS) responses. For this, we employed a standardized mouse phenotyping protocol at the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 71 publications
7
38
0
Order By: Relevance
“…Others and we previously described hyperactivity, memory impairments, and decreased anxiety in Srf mutant mice including the mouse strain used in this study . Independently of these reports, experiments performed in this study confirmed hyperactivity and less anxiety in the open field (OF) test before TBI (Figure A‐F).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Others and we previously described hyperactivity, memory impairments, and decreased anxiety in Srf mutant mice including the mouse strain used in this study . Independently of these reports, experiments performed in this study confirmed hyperactivity and less anxiety in the open field (OF) test before TBI (Figure A‐F).…”
Section: Resultssupporting
confidence: 84%
“…For this, P‐cofilin abundance––indicative of inactivated cofilin—was measured in the cerebral peduncle of sham‐ and TBI‐treated animals. In wt animals, cofilin was not phosphorylated in both sham‐ and TBI‐treated animals suggesting no obvious regulation of this actin regulator by TBI (Figure I,K,P) as also seen for acute stress exposure . In opposite to this, P‐cofilin levels were significantly upregulated upon SRF deletion ( P = .67 for wt sham vs Srf ko sham and P = .0017 for wt TBI vs Srf ko TBI; Kruskall–Wallace with DMC; Figure J,L,P).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations